2013
DOI: 10.1177/2158244013499143
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of English Colonial Terrorism and Genocide on Indigenous/Black Australians

Abstract: This article critically explores the essence of colonial terrorism and its consequences on the indigenous people of Australia during their colonization and incorporation into the European-dominated racialized capitalist world system in the late 18th century. It uses multidimensional, comparative methods, and critical approaches to explain the dynamic interplay among social structures, human agency, and terror to explain the connection between terrorism and the emergence of the capitalist world system or global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…While later ruled a legal fiction in the seminal Mabo v Queensland case [61], colonial powers relied on terra nullius to justify their takings of uncultivated, "wilderness" well into the 20 th century [62]. Thus, the fact that indigenous hunter-gatherer communities did not use territories in the same way as Europeans served as a pretext to treat such lands as "unoccupied" and thus free for the taking [63]. Of course, just because the land was being used differently did not mean that it was uninhabited or unoccupied [55].…”
Section: Primacy Of Land Cultivationmentioning
confidence: 99%
“…While later ruled a legal fiction in the seminal Mabo v Queensland case [61], colonial powers relied on terra nullius to justify their takings of uncultivated, "wilderness" well into the 20 th century [62]. Thus, the fact that indigenous hunter-gatherer communities did not use territories in the same way as Europeans served as a pretext to treat such lands as "unoccupied" and thus free for the taking [63]. Of course, just because the land was being used differently did not mean that it was uninhabited or unoccupied [55].…”
Section: Primacy Of Land Cultivationmentioning
confidence: 99%
“…You have to break numbers down first to those who died through slavery (Stannard, 1993), and then colonisation, frontier wars and also invasion (Tharoor, 2016). The reason being that in what research I have found, the twoslavery and colonisationare not listed together; and finally, what had started this discussion in having to also consider biological warfare, both intentional and unintentional, through the spread of influenza and other viruses (Jalata, 2013). When you add the three together you start getting some idea of the devastation caused to black and Aboriginal races around the world.…”
Section: Notementioning
confidence: 99%
“…These stereotypes that aid in the repression and ongoing attempted genocide that Indigenous peoples endure in turn allow for other harmful concepts to come into play. The idea of terra nullius (nobody's land) evolved from a settler colonial desire to occupy land; land was newly created as 'uninhabited' by the act of deeming any existing communities as insignificant or null, such as those of "savages," which then allowed for the extraction of valuable resources, the usurping of property, and other colonial enterprises (Lindqvist, 2007;Jalata, 2013). Many areas around the world, including the Pacific Islands, have and continue to experience settler colonialism expressed through both racial oppression and capitalist exploitation (Batur and Weber 2017; Batur 2018).…”
Section: Imperialism and Settler Colonialism In The Pacificmentioning
confidence: 99%